Optical microfiber refractometric sensors - Ji, Wenbin (2017)
In this study, the author has investigated two types of microfibers, namely the adiabatically (gradually) tapered and non-adiabatically (abruptly) tapered microfibers. For the adiabatic microfiber, the fiber is tapered gradually so that only the fundamental mode will propagate inside the fiber. Thus, the transmission spectrum of such microfiber is as flat as before it was tapered. Hence to use this type of fiber as a refractive index sensor, there is a need to incorporate other techniques in the microfiber to generate a reference wavelength such as resonant dip or peak so that the wavelength response due to external refractive index variation can be interrogated. In this project, the author has adopted two ways for doing this. One is to inscribe a fiber Bragg grating (FBG) and another is to inscribe a long period grating (LPG) in tapered portion of the photosensitive fiber. Both these two gratings were written into the taper waist portion using a KrF eximer laser. There is a wavelength peak in the reflection spectrum of microfiber Bragg grating (MFBG) and a wavelength dip in the transmission spectrum of microfiber long period grating (MLPG). The resonant peak and dip shift when the external refractive index changes. The RI sensitivity of MFBG was found to be moderate (~80 nm/RIU) as compared to other RI sensors while the sensitivity of MLPG (~600 nm/RIU) was much higher than normal LPG RI sensors. The other type of microfiber is the non-adiabatic microfiber, where the fiber taper slope is steep. As a result, higher-order modes are excited as light propagates down the fiber. The induced higher-order modes will interfere with the fundamental mode resulting in a sinusoidal wavelength response. The wavelengths will shift as the external refractive index (RI) increases. In the experiment, the diameter of the microfiber was reduced up to 4.6 μm and the sensitivity was found to be extremely high, of around 50,000 nm/RIU. The author also has developed a numerical model that can predict the behavior of such non-adiabatically tapered microfiber. It is also worth mentioning that generally the smaller diameter microfiber gives a higher sensitivity as more evanescent field will be coupled to the surrounding medium. For the adiabatic microfiber sensors, although a smaller diameter is shown to be more sensitive, it is difficult to obtain very small diameters of few micrometers as the taper transitions need to be sufficiently long to maintain single mode in the microfiber. And since the abruptly tapered fiber can be fabricated with a much smaller diameter, it is thus easier to obtain higher sensitivity with it as compared to the gradually tapered fiber. One common issue in interferometric based sensors is the free spectral range (FSR), as such sensors will not work properly once the resonant wavelengths shift over one cycle of the FSR. For tapered microfiber, it was found that the temperature and the pulling speed during the tapering process are the crucial control parameters to achieve the desired tapered profile. By setting a cooler tapering temperature and fast pulling speed, ultra-short microfibers with waist length of only 2.4 mm and total length of 5.5 mm were successfully fabricated. The resulting FSR is around 80 nm and the maximum sensitivity achieved for such short microfiber is 25,667 nm/RIU. The above optimization work for the abruptly tapered microfiber sensor makes such sensor very useful in real applications. Heavy metal pollution in natural water environment is always a concern in both human health and our environment. All current systems available in the market for detecting heavy metal ions have common drawbacks such as bulky size, expensive set-up and costly maintenance. As a wrap up of my work, the author also presented an application of the optical microfiber sensor functionalized with chelating agent to detect the existence of specific heavy metal ions in water. A clear spectral shift was observed when the sensor was immersed into metal ion solution, and the minimum resolution achieved for copper ion can be as low as 10 parts per billion (ppb), utilizing a 3.9 um diameter fiber functionalized with the chelating agent D-Penicillamine (DPA).